Benign symptomatic glial cysts of the pineal gland: a report of seven cases and review of the literature. Issue 8 (August 1989) - Klein, P; Rubinstein, L J
Abstract : Seven cases of clinically symptomatic benign glial cyst of the pineal gland are reported. The cysts' size ranged from 1.0-4.5 cm in diameter. They were characterised by a golden or, less frequently, brown-reddish proteinaceous or haemorrhagic fluid content. The cyst wall, up to 2 mm thick, consisted of clusters of normal pineal parenchymal cells, often compressed and distorted, surrounded by reactive gliotic tissue which sometimes contained Rosenthal fibres. The presenting clinical features included headache (6/7), signs of raised intracranial pressure, partial or complete Parinaud's syndrome (5/7), cerebellar deficits (2/7), corticospinal and corticopontine fibre (2/7) or sensory (1/7) deficits, and emotional disturbances (2/7). CT and MRI (in 2/7 cases) scans showed a hypodense or nonhomogeneous lesion in the region of the pineal gland, with or without contrast enhancement. Surgical excision resulted in complete clearance of the symptoms in 5/7 patients. The previous literature is reviewed and the clinicopathological correlations and the possible pathogenetic mechanisms are discussed. The need to distinguish this benign lesion from other mass lesions of the pineal region, in particular from pinealocytoma, is stressed.